539 High dimensional analysis of the human lymph node during melanoma progression reveals shifts in myeloid content that relate to differential T cell content. (9th November 2020) - Prokopi, Anastasia; Lopez-Gonzalez, Marta; Verhoeff, Jan; Ven, Rieneke Van de; Garcia-Vallejo, Juan; Stoitzner, Patrizia; Gruijl, Tanja de
Abstract : Background: The sentinel lymph node (SLN) in melanoma represents the crossroads of the initiation of effector T cell responses and of lymphatic metastasis of the primary tumor. As such, alterations in the human LN immune cell network during melanoma progression are of particular interest for the development of effective immunotherapeutic approaches for each stage of disease. Methods: We used mass cytometry (CyTOF) and multiparameter flow cytometry to characterize the alterations in the major immune populations in the human LN. We included LN derived from healthy donors (n=10), tumor-negative (SLN-, n=7) and tumor-positive SLN (SLN+, n=3) and LN metastatic samples (n=4). Results: Our results show that melanoma progression in the LN is accompanied by increased relative frequencies of myeloid cells, B cells and NK cells whereas T cell rates are significantly decreased. More specifically, for the myeloid cells we observed a decrease in frequencies of migratory cDC subsets and of LN-resident cDC and macrophage subsets in the SLN accompanying early melanoma development and metastasis. In fully metastatic LN from patients with advanced melanoma, a clear predominance of inflammatory, monocyte-derived subsets was observed. Simultaneously with this shift in myeloid subsets, an increase in CD4+ Tregs and CD8+ effector T cell subsets became apparent with metastatic progression in the LN. Both Tregs and CD8+ effector T cells in LN metastases were further characterized by relatively high expression of PD-1 and TIGIT immune checkpoints. Conclusions: The changes observed in the myeloid compartment accompanying metastatic progression in melanoma-draining LN, were found to be related to the shifts in lymphocytic subsets and their differentiation and activation state. Our results provide insights into the steady-state immune characteristics of the healthy human LN and identify all the changes that accompany melanoma progression through the different stages and give important clues about possible therapeutic interventions, aiming at immune potentiation of the SLN.